2008
DOI: 10.1007/s10800-008-9480-z
|View full text |Cite
|
Sign up to set email alerts
|

Structure, mechanical and corrosion properties of DC reactive magnetron sputtered aluminum nitride (AlN) hard coatings on mild steel substrates

Abstract: Aluminum nitride (AlN) coatings of about 2 lm thick were deposited on mild steel (MS) by means of direct current (DC) reactive magnetron sputtering. AlN coatings were prepared in an Ar + N 2 gas mixture and their crystal structure, microstructure, and topography were analyzed by X-ray diffractometry (XRD), scanning electron microscopy (SEM) and atomic force microscopy (AFM), respectively. XRD revealed that the films are polycrystalline in nature and have a hexagonal wurtzite structure with a predominant peak o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Nevertheless, making bulk AlN often requires sintering at very high temperatures under controlled atmosphere, which is not economically feasible. AlN thin films offering an alternative to the bulk AlN are often produced by reactive magnetron sputtering . Conventionally making such nitride films, similar to other nitride thin films, requires a low base pressure (high vacuum) before sputtering to minimize the influences of residual gases that may cause the formation of oxide or oxynitride overlayers.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, making bulk AlN often requires sintering at very high temperatures under controlled atmosphere, which is not economically feasible. AlN thin films offering an alternative to the bulk AlN are often produced by reactive magnetron sputtering . Conventionally making such nitride films, similar to other nitride thin films, requires a low base pressure (high vacuum) before sputtering to minimize the influences of residual gases that may cause the formation of oxide or oxynitride overlayers.…”
Section: Introductionmentioning
confidence: 99%
“…In the TEM image, the precipitates are marked with white arrows. The SAED pattern revealed that the lattice parameter was 0.246 nm, corresponding to the AlN hexagonal wurtzite crystal structure [35]. Figure 8b shows the elemental distribution maps for Fe, Al, and N using the EELS analysis at the red box in Figure 8a.…”
Section: Resultsmentioning
confidence: 99%
“…Lӧbl et al [24] and Treichel and Kirchhoff [25] have demonstrated that the substrate temperature and the energy of the particles impinging on the substrate were the two key factors, for the crystallization of the sputtered film. During DC reactive magnetron sputtering the particles generally impinge on the substrate with 1-10 eV energy [26], which facilitates the crystallization of sputtered TiN/NbN multilayered coating. Increase in substrate temperature to 400 °C causes the TiN/NbN multilayered coatings to exhibit a strong orientation along (111)/(101) and other peaks (200)/(103), (220)/(106), and (222)/(108) as well.…”
Section: Resultsmentioning
confidence: 99%